2022
DOI: 10.1007/s11030-022-10468-8
|View full text |Cite
|
Sign up to set email alerts
|

Targeting SARS-CoV-2 non-structural protein 13 via helicase-inhibitor-repurposing and non-structural protein 16 through pharmacophore-based screening

Abstract: Novel drug compound hunting was carried out for SARS-CoV-2 proteins with low mutation susceptibility. The probability of escape mutation and drug resistance is lower if conserved microbial proteins are targeted by therapeutic drugs. Mutation rate of all SARS-CoV-2 proteins were analyzed via multiple sequence alignment Non-Structural Protein 13 and Non-Structural Protein 16 were selected for the current study due to low mutation rate among viral strains and significant functionality. Cross-species mutation rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…The specified concentration of Nsp13 (see Figure Legends ) was pre-incubated with 0.25 nM RNA partial duplex containing the specified number of bp ( 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ) for 5 min at RT in 20 mM HEPES-KOH (pH 7.5), 20 mM NaCl, 1 mM DTT, 100 μg/mL BSA and the indicated concentration of MgCl 2 , as noted in the Figure Legends . Reactions were initiated by the addition of 2 mM ATP, 5 nM unlabeled oligonucleotide (same as radio-labeled oligonucleotide), and 100 nM dT 200 protein trap.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The specified concentration of Nsp13 (see Figure Legends ) was pre-incubated with 0.25 nM RNA partial duplex containing the specified number of bp ( 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ) for 5 min at RT in 20 mM HEPES-KOH (pH 7.5), 20 mM NaCl, 1 mM DTT, 100 μg/mL BSA and the indicated concentration of MgCl 2 , as noted in the Figure Legends . Reactions were initiated by the addition of 2 mM ATP, 5 nM unlabeled oligonucleotide (same as radio-labeled oligonucleotide), and 100 nM dT 200 protein trap.…”
Section: Methodsmentioning
confidence: 99%
“…Nsp13 helicases from SARS-CoV and SARS-CoV-2 differ by just one amino acid at residue 570 (Isoleucine in SARS-CoV and Valine in SARS-CoV-2) ( 17 ). An alignment of Nsp13 from SARS BJ01 and Bat SARS-like coronavirus show over 99% similarity as well ( 18 ). Nsp13 has a low mutation rate with only 23 mutations observed in a sample of 439 SARS-CoV-2 viral strains ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SARS-CoV-2 helicase has been screened, virtually, in many instances ( Supplementary Table S3 ). From our analysis it was observed that most publications have performed virtual screening on commercially available drugs ( Balasubramaniam and Schmookler Reis 2020 ; Borgio et al, 2020 ; Gurung 2020 ; Iftikhar et al, 2020 ; Ugurel et al, 2020 ; Abidi et al, 2021 ; Sundar et al, 2021 ; Alanazi et al, 2022 ; Azmoodeh et al, 2022 ) or natural products ( Kousar et al, 2020 ; Naik et al, 2020 ; Ahmad et al, 2021 ; James et al, 2021 ; Vivek-Ananth et al, 2021 ; Bhargavi et al, 2022 ; Hossain et al, 2022 ; Samdani et al, 2022 ). Other published works make use of fragments ( Freidel and Armen, 2021 ) or publicly available compound libraries ( Mirza and Froeyen, 2020 ; García et al, 2021 ; El Hassab et al, 2022 ; Pitsillou et al, 2022 ).…”
Section: Main Considerationsmentioning
confidence: 99%
“…The antiviral efficacy against influenza A virus and human papillomavirus of tannins from Hamamelis virginiana bark extract has also been demonstrated [ 32 ]. Gallotannin 1 has also become a relatively successful molecule in various in silico screening models aimed at studying the inhibition of proteins important in the process of carcinogenesis, atherosclerosis, or SARS-CoV-2 disease [ 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%